Applicability of Solid Lubricant Coatings in Cold Rod Extrusion of Stainless Steels - Jobst, Andreas; Merklein, Marion (Defect and Diffusion Forum, 2020)
Cold extrusion is an established technology for the production of dimensionally accurate components in large series. Due to the high material and energy efficiency, a resource-saving manufacturing of high-performance parts is possible. Forming at room temperature leads to an advantageous grain structure and work hardening of the material, resulting in components with favorable operating characteristics. Nevertheless, a challenge is the generation of residual stresses during forming, which are influencing the fatigue behavior. The modification of the tribological conditions is one method for influencing the parts’ residual stress state. However, the high strength and work hardening of the materials formed at room temperature leads to high tribological loads between billet and die. These challenges are intensified by the increasing use of stainless steels due to growing demands for corrosion resistant components. The aim followed within this paper is therefore to investigate the applicability of typical lubricant coatings in the forward rod extrusion of stainless steels. For this purpose, the ferritic stainless steel X6Cr17 (DIN 1.4016) and the ferritic-austenitic stainless steel X2CrNiMoN22-5-3 (DIN 1.4462) are extruded with an equivalent plastic strain of ε̅ ≈ 1. The research is performed with a molybdenum disulfide (MoS2), a soap and a polymer-based lubricant coating. For reproducing different contact conditions, the die geometry is varied with die opening angles of 60°, 90° and 120°. The suitability of the lubricants is evaluated using the integrity of the lubricant coating after forming. From the correlations between process forces, temperatures and surface integrity, recommendations for the application of the researched lubricants are derived.

Component residual stress control in forward rod extrusion by material flow and tribology—experiments and modeling - Jobst, Andreas; Floros, Dimosthenis; Steinmann, Paul; Merklein, Marion (Forschung Im Ingenieurwesen-Engineering Research, 2021)
The forward rod extrusion of ferritic stainless steel X6Cr17 (DIN 1.4016) is here investigated with the objectives to experimentally identify and numerically verify the effect of the lubrication system and die opening angle on residual stresses. Three lubricants – MoS2, soap and polymer – are considered whose tribological properties are characterized via double cup extrusion tests. The effect of material flow is also studied by forming in conical dies featuring three different opening angles. The extrusion experiments revealed a decrease in the near-surface tensile stresses with decreasing friction for all the considered opening angles. An opening angle of 2α = 90° led to the highest tensile residual stresses. Both an increase to 2α = 120° and a decrease to 60° resulted in reduced tensile stresses and even a shift to compressive stresses. Furthermore, a previously developed numerical model of forward rod extrusion is optimized and validated against the experimentally measured residual stresses. The effect of the spatial and temporal discretizations of the model on the predicted residual stresses is investigated. Based on the experimental and numerically verified results, the recommendation to reduce friction in forward rod extrusion is derived as a means to obtain a less detrimental to the lifecycle of extruded parts residual stress state.

Eigenspannungen beim Voll-Vorwärts-Fließpressen – Entstehung, Einstellung und Stabilität - Jobst, Andreas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2024)
Kaltmassivumformverfahren wie das Voll-Vorwärts-Fließpressen werden als ressourcen- und energieeffiziente Fertigungsmethode für metallische Bauteile eingesetzt. Inhomogene plastische Dehnungsverteilungen, die dabei typischerweise auftreten, führen jedoch zum Verbleiben von Eigenspannungen im Werkstoff, welche zu unerwünschten Effekten führen und das Ermüdungsverhalten maßgeblich beeinflussen können. Das in dieser Arbeit verfolgte Ziel ist die Erarbeitung einer Methode zur eigenspannungssensitiven Prozessauslegung. Anhand eines Referenzprozesses wurde die Eigenspannungsentstehung beim Voll-Vorwärts-Fließpressen des rostfreien Stahls X6Cr17 numerisch und experimentell untersucht. Darauf aufbauend wurden Steuer- und Störgrößen zur Eigenspannungseinstellung qualifiziert und deren Auswirkungen quantifiziert. Unter zyklisch-mechanischer Bauteilbelastung wurden verschiedene Relaxationsmuster identifiziert. Hinsichtlich der thermischen Belastung wurde ein Prozessfenster erarbeitet, innerhalb dessen stabile Eigenspannungen vorliegen. Darauf aufbauend wurde ein modellbasierter Zusammenhang zwischen der Temperatur, der Belastungsdauer und der Eigenspannungsstabilität abgeleitet. Es konnte gezeigt werden, dass eine Beeinflussung der Betriebsfestigkeit fließgepresster Bauteile durch die Eigenspannungssteuerung bei der Umformung möglich ist. Durch eine Anpassung des Matrizendesigns konnten kostengünstig oberflächennahe Zugeigenspannungen reduziert und die Langzeitfestigkeit erhöht werd

Forming of complex functional elements on sheet metal - Reck, Manuel; Rohrmoser, Andreas; Jobst, Andreas; Pilz, Florian; Merklein, Marion (Sheet Bulk Metal Forming, 2021)

Influence of dry ice blasting process properties on surface roughness and residual stresses of machined and additive manufactured workpieces - Amon, Sven; Jobst, Andreas; Merklein, Marion; Hanenkamp, Nico (Procedia CIRP, 2022)
Dry ice blasting has shown the potential to remove metallic burrs after machining processes and support structures after additive manufacturing. During blasting, process parameters need to be chosen depending on the material and the geometric properties of the burr. However, dry ice blasting affects the local material properties on a micro level and improper blasting parameters may lead to changes in the part surface. In this article, correlations and interactions between dry ice blasting parameters and resulting specimen roughness and residual stresses are identified for machined and additive manufactured metallic materials.<br
Keywords: dry ice blasting; metallic edge zone; deburring; post-processing; residual stresses

Influence of Material Delivery Condition on Residual Stresses and Part Properties During Forward Rod Extrusion - Jobst, Andreas; Merklein, Marion (13th International Conference on the Technology of Plasticity, 2021)
During the manufacturing of semi-finished products, the material is subjected to various forming steps to achieve the final geometry. In order to reduce the work hardening introduced and to ensure a good formability, it is annealed before component manufacturing. Forming technologies like forward rod extrusion are well-established methods for the efficient production of resilient components. In this process, however, an inhomogeneous pre-strengthening of the material influences the stress distribution during forming and therefore the mechanical properties and the residual stresses in the component. Since they affect the parts’ operating behaviour, knowledge of the influence of the delivery condition of the material is necessary. The aim of this paper is to derive dependencies between material properties and the resulting residual stresses and work hardening in the component. Due to the increasing application, ferritic stainless steel X6Cr17 in the skin passed (+LC) and soft annealed (+A) states are used. Residual stresses, microstructure, and microhardness distribution of both material states are compared regarding the rods and extruded parts. The effects of the delivery condition are evaluated by comparing process and component properties.
Keywords: Forward extrusion; Material condition; Stainless steel; Residual stress; Work hardening

Investigations on Residual Stress Generation in Extruded Steel Components - Jobst, Andreas; Kiener, Christoph; Merklein, Marion (9th Congress of the German Academic Association for Production Technology (WGP), 2019)
During the forming of components, inhomogeneous stress conditions lead to residual stresses, which influence the operating behaviour of the manufactured part. Compressive residual stresses generally have a positive effect, while tensile residual stresses reduce the fatigue strength and facilitate crack initiation. Full forward extrusion has been established as an industrial manufacturing technique, where cylindrical billets are formed in the die and ejected in opposite direction. In order to influence the residual stresses state, it is essential to know about its formation. A basic understanding is created by separate investigation of the forming and the ejection step. In the context of this paper, singlephase ferritic stainless steel X6Cr17 and ferritic-austenitic duplex steel X2CrNi- MoN22-5-3 are used. The quantification of the residual stresses states is carried out by X-ray diffractometry, for which a measurement method for duplex steel is validated. The influence of forming and ejection is determined separately by manufacturing components with and without an ejection operation.<br
Keywords: Residual Stress; Forward Extrusion; Stainless Steel

Investigations on residual stress generation in full-forward-extrusion - Landkammer, Philipp; Jobst, Andreas; Kiener, Christoph; Steinmann, Paul; Merklein, Marion (Production Engineering, 2019)
Within cold-forming processes, the influence of forming induced residual stresses is a critical issue regarding the life-time behaviour of the formed components. However, a targeted use of forming-induced residual stresses is also capable to improve the components properties. The rotation-symmetrical full-forward extrusion is used as a reference process to investigate the generation of residual stresses within manufacturing. A novel and generally applicable computational evaluation procedure is introduced, which achieves to compute and visualize the evolution of the residual stress state during the entire forming operation. Simulative results are compared with their experimental counterparts. The near-surface residual stresses in the formed component are evaluated in axial and tangential direction by X-ray diffraction. Indentation tests are used to determine the micro-hardness inside the components and optical instruments quantify geometrical difference
Keywords: Residual stresses· Full-forward-extrusion· Experimental validation· Advanced post processing

Mechanisms of residual stress generation in full-forward-extrusion - Landkammer, Philipp; Jobst, Andreas; Kiener, Christoph; Steinmann, Paul; Merklein, Marion (Production Engineering, 2019)
LFT Import::2019-07-29 (2366)

Stability of forming induced residual stresses in stainless steel components under mechanical load - Jobst, Andreas; Merklein, Marion (Manufacturing Letters, 2023)
Cold forward extrusion leads to the generation of residual stresses, which can have an advantageous or detrimental effect on the operating behavior of the formed components. In industrial practice, energy-intensive annealing steps are often used to remove unknown stress states and thus prevent unexpected failures. Residual stress-related knowledge can therefore help to save energy and resources. To be able to estimate the effects, not only sign and magnitude need to be known, but also the residual stress stability under typical operating loads. In this paper, stainless steel X6Cr17 (DIN 1.4016, AISI 430) is formed by forward rod extrusion at room temperature. The forming process leads to residual stresses in the formed components, which are subsequently subjected to mechanical testing. To represent different initial states, components with varied die opening angles are produced and tested. A modified 3-point bending setup is used to generate a defined tensile load stress in the part surface. The results show a behavior of the residual stresses, which is depending on the load magnitude, the initial stress state and the work hardening distribution in the part. While the number of cycles has an influence, the largest changes occur in the first stroke.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Extrusion; Residual stress; Stability; Stainless steel

Stability of forming induced residual stresses in stainless steel parts at elevated temperature - Jobst, Andreas; Merklein, Marion (ICRS11 - 11th International Conference on Residual Stresses, 2023)

Strategies for residual stress adjustment in bulk metal forming - Franceschi, A.; Stahl, J.; Kock, C.; Selbmann, R.; Ortmann-Ishkina, S.; Jobst, Andreas; Merklein, Marion; Kuhfuss, B.; Bergmann, M.; Behrens, B. -A.; Volk, W.; Groche, P. (Archive of Applied Mechanics, 2021)
The family of bulk forming technologies comprises processes characterised by a complex three-dimensional stress and strain state. Besides shape and material properties, also residual stresses are modified during a bulk metal forming process. The state of residual stresses affects important properties, like fatigue behaviour and corrosion resistance. An adjustment of the residual stresses is possible through subsequent process steps such as heat treatments or mechanical surface modification technologies, like shot peening and deep rolling. However, these additional manufacturing steps involve supplementary costs, longer manufacturing times and harmful effects on the product quality. Therefore, an optimized strategy consists in a targeted introduction of residual stresses during the forming processes. To enable this approach, a fundamental understanding of the underlying mechanisms of residual stress generation in dependence of the forming parameters is necessary. The current state of the art is reviewed in this paper. Strategies for the manipulation of the residual stresses in different bulk forming processes are classified according to the underlying principles of process modification.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Bulk forming; Cold forming; Hot forming; Manufacturing; Residual stress

Towards an holistic account on residual stresses in full-forward extruded rods: Experiment, modeling and simulation of forming and operation phases - Floros, Dimosthenis; Jobst, Andreas; Kergaßner, Andreas; Merklein, Marion; Steinmann, Paul (Archive of Applied Mechanics, 2021)
An holistic view is attempted towards prediction of the effect of residual stresses induced by full-forward extrusion on fatigue life of workpieces during operation. To study the effect of constitutive model on the accuracy of forming simulations, a combined nonlinear isotropic/kinematic hardening model as well as the isotropic hardening part of the same model are calibrated based on five compression-tension-compression uniaxial stress experiments. A full-forward extrusion finite element model is developed adapting both the aforementioned hardening plasticity models and the predicted residual stress states at the surface of the workpiece are compared against that of a corresponding forming experiment. Results show residual stress predictions of remarkable accuracy by the FE-models with the isotropic hardening model. The effect of residual stresses on fatigue life of the workpiece is qualitatively studied by uncoupled multiscale simulations featuring gradient crystal plasticity at the microscale. While the effective (homogenized) macroscale response indicates elastic response during a macroscopically cyclic loading, plasticity accompanying reduction of residual stresses is still present at the microscale within, e.g. grain boundaries.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Cold forming; FE-simulations; Kinematic hardening; Multiscale modeling; Residual stress